Assessment of weeds as alternative hosts of plant-parasitic nematodes in coffee plantations in Costa Rica - Peraza-Padilla, Walter; Orozco-Aceves, Martha (Agronomía Mesoamericana, 2018)
There is potential for weeds to be alternative hosts of plant-parasitic nematodes (PPN), but a methodology that assesses the phytosanitary risk derived from the presence of weeds in plantations is not available. This research was conducted in order to determine if the presence of weeds in coffee plantations (organic and conventional) represented a phytosanitary risk due to their role as alternative hosts of PPN. The research was developed into two plantation located in Aserrí, San José, Costa Rica during August, 2010. The most important weeds were identified in the plantations, also nematodes of the genera Meloidogyne, Pratylenchus and Helicotylenchus were quantified in soil and roots from selected weeds and coffee plants. A permutational analysis of variance was executed in order to determine the genera of PPN that significantly differed from the ones found in weeds to the ones found in coffee plants. Based on these results, the weeds were classified as: reservoir, trap crop, or weak host of PPN. This classification criterion, in addition to life cycle and type of parasitism of the PPN were used to assign numerical values to the weeds. The values were used to calculate the Phytosanitary Risk Index (PRI) that acquired a maximum value of 10 for the weed Piper umbellatum in the organic plantation, and a maximum value of 24 for Commelina diffusa, Emilia fosbergii, Spananthe paniculata, Delilia biflora, and Spermacoce hirta in the conventional plantation. The results indicated that from a nematological perspective the presence of these weeds in coffee plantation could be a potential risk for coffee plants